Main consequences and diseases related to augmentation mammoplasty using silicone prosthesis - de Oliveira, Ana Luisa; Sahium, Gabriel Soares; Donato, Samara Alves Carolina; da Conceição, Humberto Novais; Gorgen, Indiara Maria Távora (Seven Editora, 2023)
Currently, several reports defend and encourage breast augmentation with the use of breast prostheses without also bringing consent to the risks generated by this. Even with little epidemiological data on the risks generated, even if the patient decides to opt for surgery, it is the plastic surgeon's responsibility to know and offer knowledge to the patient who opts for the implant. DOI: https://doi.org/10.56238/devopinterscie-039